Effect of population density on oviposition, development, and survival of Alloeocranum biannulipes (Hemiptera: Reduviidae) preying on Dinoderus porcellus (Coleoptera: Bostrichidae) - Loko, Y.; Toffa, J.; Gavoedo, D.M.; Kitherian, S.; Orobiyi, A.; Tamò, Manuele (Springer, 2022)
Background Alloeocranum biannulipes Montr. and Sign.(Hemiptera: Reduviidae) is a predator present in stored yam chips and a promising biological control agent against Dinoderus porcellus Lesne (Coleoptera: Bostrichidae). Numerical responses of A. biannulipes to different densities (1, 2, 4, 6, and 8) of D. porcellus larvae were evaluated under ambient laboratory conditions (T°: 25 ± 2 °C; RH: 75–80%; photoperiod 12:12 h (L/D)). The number of consumed prey, duration of pre-oviposition and oviposition, number of eggs laid, pre-imaginal development times and mortality rate of the predator were recorded.